2016
DOI: 10.1055/s-0042-108209
|View full text |Cite
|
Sign up to set email alerts
|

A Hydroalcoholic Extract from Paullinia pinnata L. Roots Exerts Anthelmintic Activity against Free-Living and Parasitic Nematodes

Abstract: Paullinia pinnata is a medicinal plant traditionally used in West Africa against a wide range of diseases including soil-transmitted helminthiases. In this study, a hydroethanolic root extract was investigated for its phytochemical composition and in vitro activity against the free-living nematode Caenorhabditis elegans as well as the larval stages of the parasitic helminths Ancylostoma caninum, Haemonchus contortus, Toxocara cati, and Trichuris vulpis.LC-MS analysis of the ethanol-water (1 : 1) extract reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
(57 reference statements)
2
15
0
2
Order By: Relevance
“…Pays Trop., 74 (3): 167-175, doi: 10.19182 et McCorkle, 1989 ;McCorkle et Mathias-Mundy, 1992 ;Lans et al, 2007). La recherche scientifique a joué un rôle capital dans la mise en lumière et le développement des pratiques ethnovétérinaires à travers le monde (Tamboura et al, 1998 ;Ademola et al, 2005 ;Molan et al, 2009 ;Spiegler et al, 2016). Un grand nombre de chercheurs et de professionnels de l'élevage reconnaissent en effet la valeur et la contribution de la médecine traditionnelle vétérinaire aux différents systèmes d'élevage (Baerts et al, 2002 ;Wanzala et al, 2005).…”
Section: Résuméunclassified
See 1 more Smart Citation
“…Pays Trop., 74 (3): 167-175, doi: 10.19182 et McCorkle, 1989 ;McCorkle et Mathias-Mundy, 1992 ;Lans et al, 2007). La recherche scientifique a joué un rôle capital dans la mise en lumière et le développement des pratiques ethnovétérinaires à travers le monde (Tamboura et al, 1998 ;Ademola et al, 2005 ;Molan et al, 2009 ;Spiegler et al, 2016). Un grand nombre de chercheurs et de professionnels de l'élevage reconnaissent en effet la valeur et la contribution de la médecine traditionnelle vétérinaire aux différents systèmes d'élevage (Baerts et al, 2002 ;Wanzala et al, 2005).…”
Section: Résuméunclassified
“…, parmi lesquels la première conférence internationale en 1997 en Inde consacrée exclusivement à la ME, « Ethnoveterinary medicine: alternatives for livestock development », la conférence en Italie en 1999, « Herbs, humans and animals ethnobotany & traditional ethnoveterinary practices in Europe », et la conférence sur la ME à l'université Ahmadu Bello au Nigeria en 2000.■ CONTRIBUTION DE LA RECHERCHE SCIENTIFIQUEAu-delà des simples enquêtes ethnobotaniques ayant permis de faire connaitre le potentiel thérapeutique et zootechnique des pratiques ethnovétérinaires, la recherche scientifique a tenté de justifier les remèdes traditionnels proposés à travers des démarches scientifiques appropriées. A cet effet, plusieurs disciplines scientifiques dont la pharmacognosie, la chimie, la toxicologie, la biologie moléculaire et les sciences vétérinaires ont collaboré afin d'identifier et de vérifier l'efficacité de certains soins traditionnels apportés aux animaux d'élevage(Asuzu et Chineme 1990 ;Chandrawathani et al, 2006 ;Zhai et al, 2007 ;Spiegler et al, 2016). Le tableau I répertorie quelques plantes médicinales dont…”
unclassified
“…The dominant compounds of Paullinia pinnata, e picatechin, and procyanidin, showed anthelmintic effects against all worm species tested except A. caninum. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Early studies demonstrated that grape seeds, which are source of C1-type procyanidins, showed a neuroprotective effect [ 119 ]. Forestry waste such as leaves, roots, and bark from Annona muricate [ 126 ], Paullinia pinnata [ 127 ] and Albizia odoratissima [ 128 ] have an inhibitory effect in lipid peroxidation, pathogen growth of plants and cancer cell proliferation, respectively. Other biological activities such as anti-VIH, anti-inflammatory, antiwrinkle effects are reported for Cinnamomum zylanicum [ 129 ], coffee pulp [ 130 ], and cocoa pods [ 46 ], respectively.…”
Section: Agro-industrial Wastes and Procyanidinsmentioning
confidence: 99%